MSCT Thoracolumbal Kontras pada Suspek Metastasis Tulang Belakang: Studi Kasus di Rumah Sakit Hermina Pandanaran Semarang - Margarita Puspitawati; Dwi Rochmayanti; Yeti Kartikasari; Nanang Sulaksono; Sudiyono Sudiyono (Poltekkes Kemenkes Semarang, 2023)
Background: MSCT is a routine imaging modality for detecting bone metastases. The use of 1.25 mm slice thickness reconstruction on Thoracolumbar MSCT examination at Hermina Pandanaran Hospital is different from preliminary studies. This study aims to determine MSCT Thoracolumbar contrast with 1.25 mm slice thickness and 3D reconstruction to produce information on anatomical images in suspected cases of spinal metastases. Methods: This research was qualitative with a case study approach. The respondents were 3 radiographers, 2 radiologists, and 1 referring doctor. Data collection by observation, interviews, and document studies. Processing and data analysis used open coding and analysis to obtain conclusions. Results: The examination procedure was carried out by preparing the patient to fast for 6 hours before the examination, checking the results of ureum creatinine, filling out the informed consent and doing a skin test. Contrast media as much as 1.1-1.2 ml/kg per patient's body weight plus saline half of the amount of contrast, flow rate 2.5-3 mL/s, scan delay 25 s. DFOV 25-35cm, ASIR 40%. Reconstruction of slice thickness 1.25 mm to get more detailed results so that it could produce informative images that evaluated the spine and soft tissue. MPR and 3D reconstruction so that the image looked real bone and could be viewed 360ᵒ. Conclusions: The resulting slice thickness of 1.25mm and 3D reconstruction produced anatomical image information that could visualize bone to see destructive lytic lesions due to metastases, and visualize soft tissue such as paravertebral masses or discs.